Case Study in Covid-19 Infodemic in Indonesia - Ferdinand Eskol Tiar Sirait; Rati Sanjaya (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2021)
COVID-19 has been declared as pandemic by WHO. Indonesian government late to give official statement that made public believe in hoax, rumours, gossip, even propaganda that they got from social media and passed from one group to another. As we know, too much information or shortage of information could lead to confusing messages that eventually increase public distrust towards official statement. Consequently, people resort to social media as the only source of information. As a mass-self communication channel, the credibility of information from this source is problematic. Castell’s mass-self communication made this circle become infodemic that hamstring public trust to government. In this research, we do comparative case study on how countries (China and South Korea) tackle communication problems during the pandemic. This research is significant because it could be a reference model of crisis communication strategy when the country faces a pandemic Relying on mass media analysis and literature review, we find that China’s government uses power to control information circulation while South Korea’s generates public’s participation in social media. Indonesia as a democratic country could use this experience to gain public’s trust by doing Coomb’s SCCT for crisis situation. Doing this, Indonesia is expected to be more prepared to for the crisis communication in the future.Keywords: COVID-19, infodemic, crisis communication, case study ABSTRAKCOVID-19 telah dinyatakan sebagai pandemi oleh WHO. Pemerintah Indonesia terlambat memberikan pernyataan resmi yang membuat publik percaya pada hoax, rumor, gosip, bahkan propaganda yang mereka dapatkan dari media sosial dan diteruskan dari satu kelompok ke kelompok lain. Seperti kita ketahui, informasi yang terlalu banyak atau kekurangan informasi dapat menimbulkan pesan yang membingungkan yang pada akhirnya meningkatkan ketidakpercayaan publik terhadap pernyataan resmi. Akibatnya, masyarakat menggunakan media sosial sebagai satu-satunya sumber informasi. Sebagai saluran komunikasi massa-mandiri, kredibilitas informasi dari sumber ini bermasalah. Komunikasi massa yang dilakukan Castell membuat lingkaran ini menjadi infodemik yang melemahkan kepercayaan publik kepada pemerintah. Dalam penelitian ini, kami melakukan studi kasus komparatif tentang bagaimana negara-negara (China dan Korea Selatan) menangani masalah komunikasi selama pandemi. Penelitian ini penting karena dapat menjadi model referensi strategi komunikasi krisis ketika negara menghadapi pandemi Mengandalkan analisis media massa dan tinjauan pustaka, kami menemukan bahwa pemerintah China menggunakan kekuatan untuk mengontrol peredaran informasi sementara Korea Selatan menghasilkan partisipasi publik di media sosial. Pengalaman ini bisa dimanfaatkan Indonesia sebagai negara demokrasi untuk mendapatkan kepercayaan publik dengan melakukan SCCT Coomb untuk situasi krisis. Dengan begitu, Indonesia diharapkan lebih siap menghadapi krisis komunikasi di masa mendatang.Kata Kunci: COVID-19, infodemik, komunikasi krisis, studi kasus